Navigating dual vulnerability: a rare case of esthesioneuroblastoma in pregnancy - Chaudhary, Mamta Kumari; Kumari, Snigdha; Jain, Vanita; Bal, Amanjit; Singh, Apinderpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Esthesioneuroblastoma (ENB) is a rare malignancy of the sinonasal tract from the olfactory neuroepithelium. Our purpose is to highlight this scarcely described but aggressive tumor presenting in a unique setting where the patient is facing dual vulnerabilities: pregnancy and EBN. We report a case of a 29-year-old female (G2P1L1), 24 weeks pregnant, with a history of progressively increasing left side nasal mass with proptosis, diplopia, nasal discharge, and bleeding from the mass. MRI showed a polypoidal mass in the left nasal cavity with intraorbital and intracranial extensions. The biopsy revealed Hyams grade 2 ENB. Management included craniofacial resection of the lesion and chemoradiation. Caesarean section was performed at 32 weeks, and the patient delivered a baby with a birth weight of 1.463 kg. Early diagnosis and timely intervention, combined with a multidisciplinary approach, for craniofacial resection and chemoradiation, can yield favourable outcomes in this challenging condition.